Assessing pension-related tax expenditures in South Africa: Evidence from the 2016 retirement reform - Agustin Redonda; Christopher Axelson (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
In 2016, the South African government introduced a comprehensive reform to simplify and harmonize the pension system in order to incentivize pension savings and increase the fairness of the retirement system. Using administrative tax micro-data, we assess the impact of the 2016 reform and find that it triggered a positive impact on the extensive margin (the number of people contributing to pension funds) and a less sharp yet positive effect on the intensive margin (the average value of contributions). The reform was not effective at mitigating the regressive impact of the retirement system because the number of individuals contributing to retirement funds increased relatively more for top earners, and it has also exacerbated the gap between low- and high-income individuals on the intensive margin side. In addition, more resources were allocated to pension-related tax expenditures, which have been proven to be highly concentrated among rich earners, both before and after the reform, hence exacerbating inequality.
Keywords: H2; H3; H55; D31; 330; pension savings; tax incentives; inequality; tax expenditures; retirement